Implementing Gender Equality: a comparative analysis of women's empowerment in Rwanda and Australia through education, empowerment and mentoring - Randell, S.; Dantas, Jaya (Creative Commons, 2015)
Rwanda is recognised for its strong implementation of the Beijing Plan of Action and Millennium Development Goal 3 on gender equality and women's empowerment. Australia, as an immigrant nation, has a strong multicultural society that has taken in waves of migrants since the Second World War, who have endeavoured to quickly become contributing citizens. This paper presents case studies of seven women foundation students of the Centre for Gender, Culture and Development (CGCD) at the University of Rwanda and ten migrant women in Australia. The outstanding contribution these 2011 Master of Gender and Development (MGD) graduates have made to Rwanda and abroad in the areas of politics, public service, international and national non-government organisations, private sector and civil society were presented and showcased by two of the graduates, Donatha Gihana and Shamsi Kazimbaya and the CGCD Founding Director, Prof Shirley Randell AO. Success stories of ten migrant women in Western Australia representing government, academia, private sector, community, civil society and not-for-profit sectors who have made a difference to the communities they belong to, their work places and who also then empower other migrant women, were presented by Associate Professor Jaya Earnest. This comparative study highlights? the concepts of empowerment, resilience, peer mentoring, family and how they impact women. • Part 1 commences with concise literature on resilience, empowerment, family resilience and mentoring. • Part 2 presents the case study methodology used to highlight the life stories of the women from Rwanda and Australia. • Part 3 showcases Rwanda and the stories of seven Gender, Culture and Development graduates from the inaugural cohort of the Master in Gender and Development. • Part 4 will highlight the narratives of ten migrant women from Australia. The final section will propose some overall findings that focus on women, education and making a difference.